Citrobacter rodentium NleB Protein Inhibits Tumor Necrosis Factor (TNF) Receptor-associated Factor 3 (TRAF3) Ubiquitination to Reduce Host Type I Interferon Production - Gao, X. F.; Pham, T. H.; Feuerbacher, Leigh A.; Chen, Kangming M.; Hays, Michael P.; Singh, G.; Rueter, C.; Hurtado-Guerrero, R.; Hardwidge, Philip R. (My University, 2017)
Interferon signaling plays important roles in both intestinal homeostasis and in the host response to pathogen infection. The extent to which bacterial pathogens inhibit this host pathway is an understudied area of investigation. We characterized Citrobacter rodentium strains bearing deletions in individual type III secretion system effector genes to determine whether this pathogen inhibits the host type I IFN response and which effector is responsible. The NleB effector limited host IFN- production by inhibiting Lys(63)-linked ubiquitination of TNF receptor-associated factor 3 (TRAF3). Inhibition was dependent on the glycosyltransferase activity of NleB. GAPDH, a target of NleB during infection, bound to TRAF3 and was required for maximal TRAF3 ubiquitination. NleB glycosyltransferase activity inhibited GAPDH-TRAF3 binding, resulting in reduced TRAF3 ubiquitination. Collectively, our data reveal important interplay between GAPDH and TRAF3 and suggest a mechanism by which the NleB effector inhibits type I IFN signaling.
Citation: Gao, X. F., Pham, T. H., Feuerbacher, L. A., Chen, K. M., Hays, M. P., Singh, G., . . . Hardwidge, P. R. (2016). Citrobacter rodentium NleB Protein Inhibits Tumor Necrosis Factor (TNF) Receptor-associated Factor 3 (TRAF3) Ubiquitination to Reduce Host Type I Interferon Production. Journal of Biological Chemistry, 291(35), 18232-18238. doi:10.1074/jbc.M116.738278
Keywords: Bacterial Pathogenesis; Infection; Innate Immunity; Interferon; Signal; Transduction